DESIGN AND ANALYSIS OF COMPOSITE POWER DRIVE CAR - M.Kumaresan , A Nagarajan , P.Sweetlin , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The Electric Solar Vehicle is a single-seated vehicle powered by 750 W BLDC hub motor. Now a day, dealers of natural resources like fuel, coal etc. is facing a hard time to keep pace with the increasing demand. Therefore, to carry out this demand it is quite necessary to make a new exploration of natural resource of energy and power. Therefore, sunlight is now a day’s considered to be a source of energy which is implemented in various day to day applications. Solar energy is being used to produce electricity through sunlight. With the help of this technology we aim to make solar energy powered car in our project. The main component to build a solar car is the solar panel. The solar cells collect a portion of the sun’s energy and store it into the batteries of the solar car. Before that happens, power trackers convert the energy collected from the solar array to the proper system voltage, so that the batteries and the motor can use it. After the energy is stored in the batteries, it is available for use by the motor & motor controller to drive the car. We are going to use two set of batteries; one of which will get the electrical energy from the panel to drive the motor and another will be used as auxiliary power source which will provide required power to other electrical devices being used in the vehicle. A microcontroller can be used in this purpose which can switch to the fully recharged battery when it senses that another battery is empty or not providing enough power to drive the motor. Again, we used a complete circuitry to solve the problem of voltage fluctuation due to movement of the sun, earth or cloud etc. We used a voltage comparator, a relay circuit for and a transistor along with a diode for this purpose. Comparator compares the voltage of solar panel and the battery and then it provides the higher voltage to the transistor to activate the relay which provides the required and stable voltage to the car. However, after all these being proceeded, the motor controller adjusts the amount of energy that flows to the motor to correspond to the throttle. The motor uses that energy to drive the wheels. Preliminarily our objective would be to implement our idea on a basic prototype and afterwards with help of this prototype we can extend our future work on building a real time electric solar powered vehicle